Synthesis, Spectroscopic of Mercury (II) Mixed Ligand Complexes of Benzotriazole with Amines Ligand - Al-Jibori, Mohamed A.; Al-Doori, Luma A. (American Journal of Biomedicine and Pharmacy, 2025)
In the present work, benzotriazole (Hbta) starting complexes with Phenylmercury(II)acetate ; [PhHg(bta)] (1) were prepared. Treatment of with one mole equivalent of the amines amines= phenonthroline, bipyridene afforded mixed ligand complexes of the formula [PhHg(bta)(amines)]; amines = phen (2), bipy (3). The resulting complexes were characterized by elemental analyses, infrared spectra, 1H-NMR spectroscopy. In complexes; (1-3), benzotriazolate link to mercury through its deprotonated nitrogen atom in a monodentate fashion.